2018
DOI: 10.1155/2018/3625053
|View full text |Cite
|
Sign up to set email alerts
|

Model Test of the Reinforcement of Surface Soil by Plant Roots under the Influence of Precipitation

Abstract: We present the results of the reinforcement of plant root systems in surface soil in a model test to simulate actual precipitation conditions. In the test, Eleusine indica was selected as herbage to reinforce the soil. Based on the various moisture contents of plant roots in a pull-out test, a fitting formula describing the interfacial friction strength between the roots and soil and soil moisture content was obtained to explain the amount of slippage of the side slope during the process of rainfall. The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…They suggested that the tensile strength of root systems dynamically changes during a rainstorm, resulting in relevant reduction of the factor of safety. Wang et al (2018) [117] were also interested in the influence of moisture on the root reinforcement, but approached the problem by means of laboratory and numerical experiments. They investigated the changes in the interfacial friction between soil and grass roots during precipitation, finding that grass can delay the time of occurrence of landslide initiation, but that effect diminishes as the soil moisture increases.…”
Section: Influence Forest Structure Wildfires and Soil Moisture Gradientmentioning
confidence: 99%
See 3 more Smart Citations
“…They suggested that the tensile strength of root systems dynamically changes during a rainstorm, resulting in relevant reduction of the factor of safety. Wang et al (2018) [117] were also interested in the influence of moisture on the root reinforcement, but approached the problem by means of laboratory and numerical experiments. They investigated the changes in the interfacial friction between soil and grass roots during precipitation, finding that grass can delay the time of occurrence of landslide initiation, but that effect diminishes as the soil moisture increases.…”
Section: Influence Forest Structure Wildfires and Soil Moisture Gradientmentioning
confidence: 99%
“…Measures on Roots Roots Modeling Slope or Smaller Scale SSM Basin or Larger Scale SSM Other Abdi et al 2018 [49] x Arnone et al 2016 [87] x x Bordoni et al 2020 [102] x x x Bordoni et al 2016 [100] x x Chiaradia et al 2016 [104] x x x Chok et al 2015 [36] x x Cislaghi et al 2017 [101] x x Cislaghi et al 2017 [85] x x x Cislaghi et al 2018 [86] x Cislaghi et al 2019 [114] x x x Cuomo et al 2020 [91] x Dazio et al 2018 [57] x x Gehring et al 2019 [121] x x Giadrossich et al 2017 [48] x Gonzalez-Ollauri 2017 [99] x x x Hales et al 2018 [82] x x Hales and Miniat 2017 [43] x x x Hwang et al 2015 [81] x x x Kokutse et al 2016 [35] x x Likitlersuang et al 2017 [106] x Masi et al 2020 [70] x Moos et al 2016 [111] x x x Rickli et al 2019 [112] x Rossi et al 2017 [107] x Saadatkhah et al 2016 [93] x x Salvatici et al 2018 [89] x Schmaltz and Mergili 2018 [113] x x Schmaltz et al 2019 [116] x x Switala and Wu 2018 [95] x Switala and Wu 2019 [97] x Vergani et al 2017 [11] x Vergani et al 2017 [118] x x Vergani et al 2015 [21] x x Wang et al 2017 [105] x x x Wang et al 2018 [117] x x Wang et al 2019 [103] x In the last few years, a challenging research trend emerged in the field of slope stability modelling: the progressive widening of application areas from slope to catchment and regional scale-i.e., over dozens or hundreds of squared kilometer-wide areas. Although advances made in the modelling of the mechanica...…”
Section: Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In various regions, such as the loess region of China, northern Mexico and the Canary Islands of Spain, the relationship between vegetation and slope hydrological effects exhibits different laws 25 , 38 40 . Similarly, the hydrological effects of different vegetation types, such as bovine sinew, alfalfa, wood and ginger, are also notably different 14 , 15 , 41 , 42 , 43 . The above research results confirm that vegetation exerts its slope protection impact through hydrological effects, and the effect is strongly influenced by climate, region and vegetation type.…”
mentioning
confidence: 99%